By Toutatis! Trainee Teachers’ Motivation When Using Comics to Learn History - Moreno-Vera, Juan Ramón; Ponsoda-López de Atalaya, Santiago; Blanes-Mora, Rubén (Frontiers in Psychology, 2021)
The main goal of this research is to analyse the perception of trainee primary education teachers regarding motivation when using comics as a resource to teach and learn history. To achieve this objective, a history education programme was designed based on the use of comics and the outcomes evaluated via a mixed qualitative-quantitative post-test questionnaire (Likert scale 1 to 5). 221 trainee primary teachers from the University of Alicante, Spain participated in the study during the 2020/2021 academic year. Data was collected using the IBM SPSS v.24 statistical package and AQUAD 7. The results showed that: the majority of future teachers felt highly motivated when using comic resources to learn history instead of textbooks (90.5% of the participants); trainee teachers recognise that the use of comics improves their capacity to be more creative and that they feel able to design and use their own comic resources to teach history in the future.